The civic world of early Renaissance Florence - Brucker, Gene A. (Princeton University Press, 1977)
Professor Brucker contends that changes in the social order provide the key to understanding the transition of Florence from a medieval to a Renaissance city. In this book he shows how Florentine politics were transformed from corporate to elitist. He bases his work on a thorough examination of archival material, providing a full socio-political history that extends our knowledge of the Renaissance city-state and its development. The author describes the restructuring of the political system, showing first how the corporate entities that comprised the traditional social order had lost cohesiveness after the Black Death. He traces the process of readjustment that began during the guild regime of 1378-1382, and analyzes the impact of foreign affairs. During the crisis years of the Visconti wars the distinctive features emerged of an elitist regime whose vitality was demonstrated following the death of Giangaleazzo Visconti and whose membership and style the author discusses in detail.Originally published in 1977.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.